2021
DOI: 10.1007/s10433-020-00598-z
|View full text |Cite
|
Sign up to set email alerts
|

How do personality traits manifest in daily life of older adults?

Abstract: The present study examined how personality traits manifest in daily life of older adults and distinguished between the manifestations of experiences and behaviors. We used data from an ambulatory assessment study over 10 days with assessments of trait-related experiences and behaviors obtained from 136 older adults aged between 60 and 91 years (41.2% male; M = 70.45 years). Multilevel models revealed that on average, 61.2% of variance in trait-related experiences and 39.6% of variance in behaviors were due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…An unconditional frequency is a simple count of reported behavior, independent of context. This can for example be done by having participants fill out behavioral check-lists every day, counting how many different trait-associated behaviors were performed in total (Ringwald et al, 2022; for an empirical example see Lindner et al, 2022). The total count of behavior is then taken as the feature representing personality manifestation.…”
Section: Frequenciesmentioning
confidence: 99%
“…An unconditional frequency is a simple count of reported behavior, independent of context. This can for example be done by having participants fill out behavioral check-lists every day, counting how many different trait-associated behaviors were performed in total (Ringwald et al, 2022; for an empirical example see Lindner et al, 2022). The total count of behavior is then taken as the feature representing personality manifestation.…”
Section: Frequenciesmentioning
confidence: 99%
“…We use the term state expression to describe the extent to which people express their behavior, thoughts, and feelings at a particular time and situation in a way that is consistent with their personality traits (Baumert et al, 2017; Fleeson, 2001; Wrzus & Roberts, 2017). Numerous studies found substantial variation or fluctuations in the expressions of personality states over repeated assessments across situations (Church et al, 2013; Fleeson, 2001; Fleeson & Gallagher, 2009; Lindner et al, 2021, 2022; Noftle & Fleeson, 2010). Hence, variety in daily life may be responsible, in part, for variation in state expression.…”
Section: Introductionmentioning
confidence: 99%
“…(2) How variable is the expression of personality states in daily life? Based on previous work on state expression (Fleeson & Gallagher, 2009; Lindner et al, 2022; Wilson et al, 2017), we expected substantial within-person variation in state expression. (3) How is variety in daily life related to the expression of personality states?…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unavailability of medical treatments for age-related cognitive decline, mind-body practices (MBP), such as yoga, may be a useful option. Research has documented that personality is related to both daily activities ( Lindner et al, 2021 ) and cognition ( Graham & Lachman, 2012 ); still, its role in the association between MBP and cognition is not well understood. In this study, we examine bidirectional temporal associations between personality traits, MBP, and cognition in healthy adults.…”
Section: Introductionmentioning
confidence: 99%
“…Personality traits are related to a range of daily activities ( Lindner et al, 2021 ), including health behaviors ( Allen et al, 2019 ), physical activity ( Saklofske et al, 2007 ), and MBP ( Barkan et al, 2016 ; Jung et al, 2016 ). For example, Yu and colleagues found that personality traits have a significant positive effect on the amount of physical activity participation ( Yu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%